Development knowledge space in peasant society for lifelong learning: case study Ban Nam Yen in Thailand - Weeranuch Yamyim,; Chusak Wittayapak,; Prasit Leepreecha,; Charin Mangkang, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This research aims to synthetic knowledge space in peasant society to develop become education resources, along with the concept of a knowledge based on the reality that all spaces are learning, whether formal or non-formal and informal education. It may be different according to the situation and dimension in education. This study focused on the qualitative method, which emphasis group discussion, interview, and full observation. There are 180 households and education spaces such as Ban Nam Yen peasant society, Kok Saton Subdistrict, Dan Sai District, Loei Province which live in the northeast in Thailand. The result of the education divide in 2 issues; first found that the knowledge peasant society in Ban Nam Yen includes Lifelong Learning and learning society in peasant society. The second is the peasant society use their knowledge to develop education space s for lifelong learning. For example, the way to manage education using community-based learning or CBL, The curriculum of peasant school and tourism management with permanence agriculture by a folk philosopher for lifelong learning. The results of the study show that Ban Nam Yen society is open to welcome researchers and developers to help guide and manage the knowledge of the society to be systematic and develop the peasants society to be an agricultural learning center that focuses on organic agriculture and sustainable agriculture for the balance of the ecosystem in the society. In addition, the development of the society to be living learning resources has made Ban Nam Yen peasants society get the attention of peasants in different regions to learn about organic agriculture, conservation of local rice varieties, lifestyle and culture of the society. The arrival of tourists, academic scholars and society developers lead to collaboration and exchange of knowledge in different contexts, it causes ideas and practice to help solve problems and promote the development of learning resources in the society to enable the youth to absorb knowledge outside the classroom and have a good relationship with the society.